Gender considerations in One Health - Campbell, Zoe; Thomas, Lian F.; Galiè, Alessandra; McLeod, A.; Ngwili, Nicholas; Terfa, Zelalem (International Livestock Research Institute, 2024)
An overview on the application of gender issues in One Health research design and implementation, with a case study on Rift Valley fever vaccination of livestock in East Africa.